Estimation of probable maximum precipitation for Bargi catchment upto Jamtara dam site in Madhya Pradesh (MAUSAM, 1988)
An attempt has been made in this paper to evaluate Standard Project Storm (SPS) together with probable maximum precipitation (PMP) for various durations for Bargi catchment upto Jamtara dam site on river Narmada. Dally rainfall data In and around the catchment from 1901 to 1977 have been examined. Major rainstorms which affected the region during a period of 77 years were studied in detail and heaviest rain depths for different, durations have been estimated for the project area. From the heaviest rain depths the SPS has been derived for the project and PMP value5 have been obtained by moisture maximisation method considering surface dew point temperature data. PMP values have also been compared with return period estimates obtained by frequency analysis approach.The time distribution of 24-hr, 48-hr and 72-hr rainstorms have also been carried out to facilitate design engineers in the computation of design flood by unit hydrograph approach.